ANALISIS YURIDIS TANGGUNG JAWAB DIREKSI PERSEROAN TERBATAS ATAS PERJANJIAN KERJASAMA YANG MENGAKIBATKAN KERUGIAN NEGARA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 77 PK/PID.SUS/2015) - GEVI ADINDA PUTRI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Bismar Nasution, SH, MH2. Prof. Dr. Saidin,SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHum Lately, the management of a corporation has gotten public criticism for its unprofessionalism, inefficiency, and no transparency so that it is usually not survived. The problem is what makes their performance inefficient and not optimal. The research problems are how about the position and the role of Directors in managing a corporation, how about their liability for a cooperative agreement which causes the State’s loss, and how about the Panel of Judges’ consideration in handing down the Supreme Court’s Ruling No. 77PK/Pid.Sus/2015 stipulated in Law No. 40/2007 on Corporation concerning Directors’ Liability for a Cooperative Agreement which causes the State’s loss. The research used juridical normative and descriptive analytic method. The data were obtained from primary, secondary, and tertiary legal materials. They were gathered by conducting library research and understanding the Supreme Court’s Ruling No. 77PK/Pid.Sus/2015 and analyzed systematically qualitatively while conclusion was drawn deductively.Keywords: Liability, Directors, State’s Loss